Analytical model for solar radiation transmitting the curved transparent surface of solar greenhouse. (November 2020) - Huang, Lin; Deng, Lianhua; Li, Angui; Gao, Ran; Zhang, Linhua; Lei, Wenjun
Abstract: This study introduces and examines an improved mathematical model to calculate the total transmitted solar radiation captured by the curved surface of a solar greenhouse. The MATLAB platform is used to calculate the total solar radiation and takes reflected radiation from the outdoor ground into account, and the results were verified in a field test. First, mathematical expression to calculate the equivalent reflected transmissivity of the greenhouse curved surface is developed. The variation for different solar greenhouse aspect ratios on the equivalent transmissivities of beam radiation, scattered radiation, and ground-reflected radiation is simulated for four typical sunny days. Besides, the optimal solar greenhouse aspect ratio is determined for the different latitudes in six cities. Then, the equivalent beam transmissivity is compared between traditional simplified inclined planes and the actual curved surfaces of a specific solar greenhouse, which implies that the calculation results of curved surfaces are more accurate. Additionally, the transmitted solar radiation is calculated for both sunny and snowy days. The results indicate that the intensity of the radiation reflected from outdoor ground is in the same order of magnitude as the scattered radiation. This means reflected sunlight should not be neglected, especially for cities located at high altitudes. Highlights: Improved model for calculating greenhouse incident solar radiation was established. A mathematical expression for equivalent reflected transmissivity of greenhouse curved surface was proposed. Effects of solar greenhouse aspect ratio on equivalent transmissivity were investigated. The transmitted solar radiation of solar greenhouse were calculated on a typical climate.